The Androgen Regulation of Matrix Metalloproteases in Prostate Cancer and Its Related Tumor Microenvironment - Carmela Sorrentino; Rosa D’Angiolo; Giulia Gentile; Pia Giovannelli; Bruno Perillo; Antimo Migliaccio; Gabriella Castoria; Marzia Di Donato (Endocrines, 2023)
Prostate cancer represents the most common type of cancer among males and the second leading cause of cancer death in men in Western society. In most cases (~70%), PC has a slow and symptom-free growth, whereas it is more aggressive in the remaining patients. Current PC therapies prevalently target the proliferative function of the androgen receptor and may only be effective within short periods, beyond which the disease will progress to metastatic and castration-resistant phenotype. Preclinical and clinical studies are aimed at investigating the molecular basis for prostate cancer spreading. Although considerable efforts have been made to dissect the programs that foster prostate cancer spreading, few biomarkers predictive of metastatic phenotype have yet been identified and few therapeutic options are available for treatment of the metastatic disease. In the present paper, we will discuss innovative aspects of prostate cancer biology, which impinge on the role of cancer-associated fibroblasts and the released matrix metalloproteinases in the disease progression. Investigating these aspects might allow the discovery of clinically actionable biomarkers to target in the advanced stages of prostate cancer.